Grafting onto Different Rootstocks Influences Yield, Quality, Chemical Composition, and Bioactivities of Tomato Fruits under Greenhouse Conditions - Howaida I. Abd-Alla (Journal of Global Pharma Technology, 2020)
Objective: Grafting is a possible chemical free solution that shows several changes in plants, with the aid of vigorous rootstock. Methods: The influence of grafting on the yield and fruit quality of tomato cultivars grown under greenhouse condition was conducted during two successive seasons of 2016 and 2017. The metabolic composition of fruits of tomato Solanum lycopersicum L. Nefret hybrid (T1) grafted onto four rootstocks were identified by gas chromatography coupled to mass spectrometry (GC-MS). The levels of aspartate and alanine aminotransferases and alkaline phosphatase were analyzed for the determination of liver functions. The levels of oxidative stress markers; malondialdehyde (MDA), superoxide dismutase (SOD), and glutathione (GSH) were determined in the rat's liver tissue. Kidney function parameters of serum urea and creatinine levels were also measured. Histologic examinations of the liver and kidney tissues were also performed. Results: The effects of grafting on the vegetative growth, yield, and fruit quality characteristics, i.e., fruit weight, length, diameter, total soluble solids content and titratable acidity of T1, grafted onto four rootstocks have showed great variability.  The vegetative growth, i.e., plant height of T2, was increased when S. lycopersicum L. var. VFN (T2) was used as a rootstock.  T2 has showed no adverse effects in all biochemical parameters under investigation compared by the other treatments. Aldehydes, ketones, esters, fatty acids, terpenoids, carotenoids, phenolics and alkaloids were the main identified components and the major compound was β-ionone (13.37%) in T2. Conclusion: The nutritional content of T2 and that it has showed no alteration in oxidative stress markers, liver and kidney function tests and their histopathological patters support its safety. While, un-grafting or grafting onto Solanum melongena L. cv. Balady (T3) may be a tool to improve the crop quality. Keywords: Greenhouse-grown tomato, Grafting, GC-MS, Carotenoids, Lycopene, Polyphenols, Liver, Kidney, Histopathology.